Screening of Extraction Process and The Estimation of Total Alkaloids in Carica papaya Linn. Leaf - Sisca Devi; Meri Ropiqa; Yosi Bayu Murti; Akhmad Kharis Nugroho (Faculty of Pharmacy, Universitas Gadjah Mada, 2020)
The papaya leaf decoctions have been widely used as a traditional treatment for malaria. The alkaloid of papaya leaves, carpaine, is reported to have the antiplasmodial activity in vitro. The industrial-scale commercial product development requires the quantification of the carpaine, and total alkaloids in the papaya leave as the raw materials. This study aims to optimize the extraction process leading to the highest yield and total alkaloids. The extraction process was carried out using different methods and solvents. The first method was maceration with the water-miscible solvent of ethanol: distilled water: HCl 37% (89: 10: 1 v/v/v). The second method was maceration with the water-immiscible solvent of dichloromethane solvents in pH 8-9 with ammonium hydroxide. The third method was digestion with acid water solvent of 0.05 N HCl. The identification of alkaloids employed the analysis using Thin Layer Chromatography (TLC) and Dragendroff reagent. The quantification of carpaine used a densitometer, while the spectrophotometric method was used to estimate the total alkaloids. The results showed that despite the extraction methods used, the tested extracts confirm the alkaloids content with the highest yield of 3.09% (84.72% of total alkaloids).